2022
DOI: 10.2147/amep.s389013
|View full text |Cite
|
Sign up to set email alerts
|

Routine Application of Lung Ultrasonography in Respiratory Care: Knowledge, Perceptions, and Barriers to Instigate

Abstract: Background Lung Ultrasound (LUS) had proved to be beneficial in detecting respiratory disorders at the bedside. Understanding the important role of Respiratory Therapists (RTs) in the critical care, we aimed to assess their knowledge, perceived relevance of LUS to clinical practice, current skill gaps, and barriers to practice. Methods A cross-sectional, nationwide survey conducted among the RTs working in the Kingdom of Saudi Arabia. The validated questionnaire include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The attitude of the working professional RT regarding the need for the inclusion of LUS curriculum in RT school reflected the necessity of the same. This finding was backed by another cross-sectional study that focused on the RTs working in Saudi Arabia where the results showed the need of integrating LUS into RT curriculum [ 30 ].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The attitude of the working professional RT regarding the need for the inclusion of LUS curriculum in RT school reflected the necessity of the same. This finding was backed by another cross-sectional study that focused on the RTs working in Saudi Arabia where the results showed the need of integrating LUS into RT curriculum [ 30 ].…”
Section: Discussionmentioning
confidence: 83%
“…It is understood that the paucity of focused training and position statements specific for the RTs to perform LUS might have led to the ambiguity as reflected in the responses of the knowledge domain. Additionally, this uncertainty in the knowledge-related domain of RTs might perpetuate considering their naiveness in LUS and the infancy of the profession in some parts of the world [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations